Unsteady flow phenomena in human undulatory swimming: a numerical approach - Pacholak, S.; Hochstein, S.; Rudert, A.; Brücker, C. (Sports Biomechanics, 2014)
The undulatory underwater sequence is one of the most important phases in competitive swimming. An understanding of the recurrent vortex dynamics around the human body and their generation could therefore be used to improve swimming techniques. In order to produce a dynamic model, we applied human joint kinematics to three-dimensional (3D) body scans of a female swimmer. The flow around this dynamic model was then calculated using computational fluid dynamics with the aid of moving 3D meshes. Evaluation of the numerical results delivered by the various motion cycles identified characteristic vortex structures for each of the cycles, which exhibited increasing intensity and drag influence. At maximum thrust, drag forces appear to be 12 times higher than those of a passive gliding swimmer. As far as we know, this is the first disclosure of vortex rings merging into vortex tubes in the wake after vortex recapturing. All unsteady structures were visualized using a modified Q-criterion also incorporated into our methods. At the very least, our approach is likely to be suited to further studies examining swimmers engaging in undulatory swimming during training or competition.